A Biologically Based Self-Healing Wireless Sensor Network - Ponnusamy , Vasaki; Azween, Abdullah (2010)
As sensor nodes are highly resource constrained, energy efficient communication becomes one of the main issues to be dealt with. In sensor networks, transmission of data between nodes incurs the highest energy consumption, followed by the distance as energy consumed is directly proportional to the square of the distance between the sender and receiver. So distance in sensor networks should be given prime importance in order to reduce energy consumption. One of the potential problems with current routing protocols is that, they look for the lowest energy route and use that route for every communication. Moreover, energy depletion at sensor nodes may reduce network lifetime and eventually lead to routing holes. This issue can be overcome by proposed Biologically Inspired Mobile Agent based Sensor Network (BIMAS) architecture, resulting in a mobile Wireless Sensor Network (WSN), which will be discussed later. The mobile WSN proposed in this paper chooses an optimal mobility pattern so that nodes closer to the sink are not utilized the most and this prevents routing holes. The entire data aggregation and forwarding of data to a base station is carried out by a mobile node itself